Numerical Analysis of Potential Energy Recovery via a Thermoelectric Generator (TEG) for the Next-Generation Hybrid-Electric Regional Aircraft - Safa Sabet; Werner Gumprich; Michael Moeller; Andrés Felgueroso; Iván González Nieves; Miguel Díaz; Simone Mancin (Engineering Proceedings, 2025)
The thermal management of next-generation hybrid electric regional aircrafts poses critical challenges due to extreme heat loads, which could reach more than 2 MW and must be dissipated. This rejected heat can be used in a passive system such as Thermoelectric Generators (TEGs), which can directly convert thermal energy into electrical energy. This work is carried out in the framework of the EU Clean Aviation-funded project TheMa4HERA and it numerically explores the possibility of integrating thermoelectric (TE) technology in the next generation of regional aircrafts. Two case studies are considered: energy recovery from the outflow valve originally used to control the pressure of the cabin and the integration of TEG modules in skin heat exchangers used to partially dissipate heat coming from the fuel cells and/or from the power electronics. The results will permit us to understand the feasibility of implementing TEG technology into these specific conditions in terms of overall power generation. The findings indicate that while TEG integration in the outflow valve offers limited power density, the skin heat exchanger shows significantly higher potential for effective energy recovery.